농촌 및 낙후지역 개발사업의 추진 실태와 통합적 추진모형 구축 - 송미령 (한국농촌경제연구원, 2008)
The purpose of this study is to draw subjects in rural policies to settle an integrated pursuing model of various development programs for rural and underdeveloped regions. This study largely consists of three parts, which are (ⅰ) to make an analysis of actual condition in pursuing development programs for rural and underdeveloped regions, (ⅱ) to draw implications through the examples of foreign countries that have experiences of trying their own integrated pursuing models, and (ⅲ) to draw policy subjects to develop a Korean integrated program-pursuing model. For the analysis of actual condition, we take two steps. The first step is to analyze the present pursuing condition of development programs with government documents. In this process, the inventory of programs for rural and underdeveloped regions are operationally defined as programs from "Plans for Improving Quality of Life of People in Rural Regions" and a part of programs from the "Special Accounts for Balanced Development of Country. The second step is to verify six research questions inferred from the first-step analysis on the spot of projects. The research questions are demonstrated by means of focus group interviews and surveys which questioned the concerning bodies about the promoting state of the programs at the local government level and their opinions. Finally, this study suggests eight policy subjects on the basis of policy directions derived from the two-step analysis of actual condition. The proposed policy subjects are as follows: First, establishment of definite policy goals should be preceded. Second, it is necessary that the role of local government be rebuild up and the existing way of one-unit-based program should be avoided. Third, spatial boundaries for application of rural policies should be clearly defined. Fourth, establishment of Rural Area Plan which have binding power over the region should be institutionalized. Fifth, it is required to reorganize various laws concerning rural development programs. Sixth, evaluation system for performance management is needed. Seventh, construction of the basis of regional statistics should be proceeded in order that it can be possible to establish Rural Area Plan and to settle an evaluation system for performance management. Lastly, the most important thing is that regional bodies such as local government officials, experts and residents of the region are required to enhance their capability and positively participate in development programs. Researchers: Song, Mi-Ryung, Kim, Kwang-Sun and Kwon, In-Hye Research period: 2008. 3. - 2008. 10. E-mail address: mrsong@krei.re.kr